Don't know tough - Cranor, Eli, 1988- (Soho Crime, 2022)
"Trent Powers relocates his family from Anaheim to Arkansas to take over as head coach of the Denton Pirates, a high school football team powered by a volatile but talented running back named Billy Lowe. Billy comes from an extremely troubled home: a trailer park where he is terrorized by his unstable mother's abusive boyfriend. Billy takes out his anger on the field, and it's not long before he crosses a line. Instead of punishing him, though, Trent takes Billy into his home, hoping to protect his star player as the Pirates begin their playoff run. But when Billy's stepfather is found murdered, nothing can stop an explosive chain of violence that could tear the town apart"--